Individual Particle Characteristics, Optical Properties and Evolution of an Extreme Long-Range Transported Biomass Burning Event in the European Arctic (Ny-Ålesund, Svalbard Islands) - Mazzola, Mauro; S; Markowicz, Krzysztof; Krejci, Radovan; Traversi, Rita; Becagli, S.; Ritter, C.; Moroni, Beatrice; Cappelletti, David; Tunved, P. (Journal of Geophysical Research: Atmospheres, 2020)
125 5 Publikacja bezkosztowa